LncRNA PSR Regulates Vascular Remodeling Through Encoding a Novel Protein Arteridin. Issue 9 (22nd September 2022) - Yu, Junyi; Wang, Wei; Yang, Jining; Zhang, Ye; Gong, Xue; Luo, Hao; Cao, Nian; Xu, Zaicheng; Tian, Miao; Yang, Peili; Mei, Qiao; Chen, Zhi; et al.
Abstract : Rationale: Vascular smooth muscle cells (VSMCs) phenotype switch from contractile to proliferative phenotype is a pathological hallmark in various cardiovascular diseases. Recently, a subset of long noncoding RNAs was identified to produce functional polypeptides. However, the functional impact and regulatory mechanisms of long noncoding RNAs in VSMCs phenotype switching remain to be fully elucidated. Objectives: To illustrate the biological function and mechanism of a VSMC-enriched long noncoding RNA and its encoded peptide in VSMC phenotype switching and vascular remodeling. Results: We identified a VSMC-enriched transcript encoded by a previously uncharacterized gene, which we called phenotype switching regulator ( PSR ), which was markedly upregulated during vascular remodeling. Although PSR was annotated as a long noncoding RNA, we demonstrated that the lncPSR (PSR transcript) also encoded a protein, which we named arteridin. In VSMCs, both arteridin and lncPSR were necessary and sufficient to induce phenotype switching. Mechanistically, arteridin and lncPSR regulate downstream genes by directly interacting with a transcription factor YBX1 (Y-box binding protein 1) and modulating its nuclear translocation and chromatin targeting. Intriguingly, the PSR transcription was also robustly induced by arteridin. More importantly, the loss of PSR gene or arteridin protein significantly attenuated the vascular remodeling induced by carotid arterial injury. In addition, VSMC-specific inhibition of lncPSR using adeno-associated virus attenuated Ang II (angiotensin II)–induced hypertensive vascular remodeling. Conclusions: PSR is a VSMC-enriched gene, and its transcript IncPSR and encoded protein (arteridin) coordinately regulate transcriptional reprogramming through a shared interacting partner, YBX1. This is a previously uncharacterized regulatory circuit in VSMC phenotype switching during vascular remodeling, with lncPSR/arteridin as potential therapeutic targets for the treatment of VSMC phenotype switching–related vascular remodeling.